M Butterfly - Cronenberg, David (Warner Home Video, 2003)
The stage version of M Butterfly was a celebrated Broadway hit that won Three Tony Awards. The espionage trial that inspired it was a global sensation, a windfall of stunning revelations. Now M Butterfly soars again in a provocative film directed by David Cronenberg (Naked Lunch, The Fly) and Staring Jeremy Irons (1990 Academy Award winner as Best Actor for Reversal of Fortune) and John lone (The Last Emperor). The mysteries of love and the sting of betrayal are boldly portrayed in his fictional tale of French diplomat Rene Gallimard and Beijing Opera star Song Liling. Rene believes he's found the perfect woman. But after a love affair spanning nearly 20 years, he'll find he cannot believe anything about the beguiling, secretive singer. Rene learns Song Liling is a spy. And that is not the only shocking secret Rene's beloved "butterfly" hides.